A relação entre arte e sociedade à luz do conceito de autonomia estética de adorno - Bueno, Sinésio Ferraz [UNESP]; Sanitá, Karina Constancio [UNESP] (FapUNIFESP (SciELO), 2016)
This article analyzes the manner in which Adorno’s concept of aesthetic autonomy is manifested in the relationship between society and art. The following topics are discussed: the separation between theory and praxis, the internal logic of a work of art, the integrating power of the cultural industry in relation to works of art, and the impossibility of controlling its social effects, whether autonomous or engaged. The article also pretends to demonstrate the illusory nature of the proposition that art can be an effective instrument of politicization when utilized to engage and adapt its content to predetermined political objectives. The works of Adorno and of other commentators in the aesthetic field are used in the analysis.
The relation between art and society in the light of adorno’s concept of aesthetic autonomy
Keywords: Aesthetic theory; Critical theory; Theodor W. Adorno